Bank Guarantee Fund – a new public finance sector entity - Jacek Wantoch-Rekowski (Prawo Budżetowe Państwa i Samorządu)
This paper is devoted to a change in a catalogue of entities of a public finance sector in Poland. The change was made by adding a new body – the Bank Guarantee Fund. The author indicates which entities belong to the public finance sector in Poland and what is a ratio legis of including the Bank Guarantee Fund in it. The paper also indicates the legal status and tasks of the Bank Guarantee Fund.